Effect of maximal aerobic power on match performance in elite soccer referees - Castagna, C.; D'Ottavio, S. (The Journal of Strength and Conditioning Research, 2001)
The aim of this study was to verify whether referees' maximal aerobic power could influence competitive match exercise intensity. Eight elite-level referees (mean ± SD age, 37.6 ± 3.4 years) were each observed during 2 Serie A matches (n = 16), and the mean of each match activity was used for analysis. Match activities were monitored with encoder-equipped cameras. O2max was assessed under field conditions with a portable device during a progressive multistage protocol. The O2max of each subject was expressed in absolute terms (O2maxab, L·min1), relative terms (O2maxrel, ml·kg1·min1), and independent from body mass (O2maxind, ml·kg0.75·min1). Significance was set at p 0.05 for all measurements. Total distance covered during the match correlated significantly with O2maxind (r = 0.77) and O2maxab (r = 0.87). O2maxind, O2maxrel, and O2maxab correlated negatively (p < 0.05) with the time spent standing still during the match (r = 0.90, 0.85, and 0.86, respectively, p < 0.05). During the first half of the match, referees with higher levels of O2maxrel (r = 0.93, p < 0.05) and O2maxind (r = 0.90, p < 0.05) were able to cover more distance at medium intensity. In the second half of the match, medium-intensity distance and low-intensity time correlated significantly (p < 0.05) with O2maxab (r = 0.76) and O2maxrel (r = 0.75), respectively. The results demonstrate the positive influence of O2max in determining both the total amount of distance covered and the exercise intensity during a game. Higher levels of O2max may provide referees the opportunity to be more active and therefore closer to the action on the field during the game.